ISLAM: NEGARA, DEMOKRASI, HUKUM DAN POLITIK - Zuhraini, Zuhraini (Universitas Islam Negeri Raden Intan Lampung, 2014)
ISLAM : STATE, POLITICS, AND DEMOCRACY. Islam, as a comprehensive religion, does not recognize the dichotomy between religion and the state, politics, and democracy. As a religion, Islam possesses universal doctrines on the matter of state, politics and democracy which also become parts of thead-din al-Islami. As part of the phenomenon of civilization, culture and Islamic values are developed to be in tune with the social institutions affected by the situation and the dynamics of space and time. histrorical and socio-cultural factors and socio- Muslims also have an effect on the analysis and understanding of the universal teachings. The emergence of differences in analysis of a variety of state and political issues is caused by such different interpretations (polyinterpretable) which, finally, influences the formulation of political thoughts and practices in contemporary Muslim countries. This article tries to open up minds that Islam is not merely a ritual religion which contains a set of doctrines, but it also possesses a holistic, universal, and systematic views toward worldly life.